Efektivitas Model Pembelajaran Tutor Sebaya untuk Meningkatkan Kemampuan Membaca Al-Quran Siswa pada Mata Pelajaran Al-Quran Hadits di Madrasah Ibtidaiyah Al-Hidayah Palembang - Apriyana Apriyana; Amir Rusdi; Dian Erlina (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
The purpose of this study is to look at the implementation and effectiveness of peer tutoring learning models in improving the ability to read Al-Quran students on the Al-Quran Hadith subjects in madrasas ibtidaiyah Al-Hidayah Palembang. This type of research is field research using quantitative research approaches and the design used is quasi-experimental. The instrument of data collection was carried out by interviewing, observing, and documenting as well as analyzing the data using the T test. From the results of the research the implementation of peer tutoring learning models to improve the ability to read Al-Quran students on Al-Quran Hadith subjects in the Madrasah Ibtidaiyah Al-Hidayah Palembang The samples in this study were 60 class V (five) students, consisting of two classes, namely the VA class as the experimental class and the VB class which became the control class. From the results of the implementation of the research it can be seen that the posttest results of the experimental class students using the complete peer tutoring learning model increased the initial percentage from 13% to 83%, while the students classified as unfinished decreased in percentage from 87% to 17%. The class average has also increased from pretest by 66.067% to 82.2%. Then the ability to read Al-Quran students after the implementation of peer tutoring learning models in improving the ability to read Al-Quran students have achieved significant results because the value of to obtained by 7 this means to be greater than tt good at the 5% level of 2.00 and good at 1% level of 2.65, the null hypothesis proposed is rejected, this means that there is a significant difference between the control class and the experimental class that has shown a significant value. So the peer tutoring learning model can be said as one of the effective learning models to improve the ability to read Al-Quran students on the Al-Quran Hadith subjects in the madrasas ibtidaiyah Al-Hidayah Palembang.